Inadequate loan loss provisions : can it be detected from a distance? - Chng, Alex Loy Ngee. (2008)
The objective of our paper is to determine whether bank regulators and investors are able to detect the inadequacy of loan loss provisions by examining the relationship between macroeconomic variables and loan loss provisions in Thailand and Korea.